1974
DOI: 10.1002/j.1537-2197.1974.tb12258.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Measurements of Nuclear Dna in a Heterothallic and a Self‐fertile Isolate of the Myxomycete, Didymium Iridis

Abstract: Comparative measurements were made of the nuclear Feulgen‐DNA content of a heterothallic and a self‐fertile isolate of the myxomycete Didymium iridis. Plasmodial nuclei of both isolates contain the diploid amount of DNA. The replicated diploid (4C) values for the heterothallic and the self‐fertile isolates are 5.66 and 5.95, respectively. Myxamoebae, however, are quite dissimilar in their nuclear DNA content. Those of the heterothallic isolates, Honduran 1–2 (A1) and Panamanian 2–4 (A7), have mean values of 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
13
0

Year Published

1976
1976
1978
1978

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Therefore, myxamoebae are typically in the G 2 phase of the mitotic interphase, with the G 1 phase being very brief or totally absent. An extended G~phase, resulting in a population of haploid cells predominantly in class 2C has been reported elsewhere (Therrien, 1966;Mohberg and Rusch, 1971;Yemma and Therrien, 1972). The mean DNA content of the plasmodial nuclei is in all cases in category 4C.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Therefore, myxamoebae are typically in the G 2 phase of the mitotic interphase, with the G 1 phase being very brief or totally absent. An extended G~phase, resulting in a population of haploid cells predominantly in class 2C has been reported elsewhere (Therrien, 1966;Mohberg and Rusch, 1971;Yemma and Therrien, 1972). The mean DNA content of the plasmodial nuclei is in all cases in category 4C.…”
supporting
confidence: 66%
“…Data are presented as frequency histograms, with the number of nuclei on the ordinate and the DNA content on the abscissa. In this investigation a relative DNA content of 0.32 is equivalent to approximately 0.2 pg of DNA (Therrien, 1966). Swift's (1950) designations, C, 2C, 4C, are used to describe nuclear DNA content.…”
mentioning
confidence: 99%
“…IN A RECENT SURVEY of 27 isolates of Didymium iridis (Collins, 1976), it was shown that 11 have mating types and 16 do not. From the data presented, those in the first category are cleary sexual (heterothallic), but among the 16 which can complete their life cycle in single-myxamoeba-derived cultures, it was not determined whether the isolates are sexual (homothallic) or non-sexual (apogamic).…”
mentioning
confidence: 99%
“…On the other hand an apogamic isolate would not display alternation of haploid and diploid generations, so the DNA level in both myxamoebal and plasmodial nuclei should be the same. Furthermore, since the characteristic nuclear DNA value for several heterothallic isolates of D. iridis are known Yemma, 1974, 1975;Collins and Therrien, 1976) these were used as a standard against which we compared our new findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation